Effects of antibiotics (enrofloxacin) on microbial community of water and sediment in an aquatic ecological model - Dai, Yue; Peng, Jin-Ju; Zhang, Teng-Yue; Xie, Xing-Peng; Luo, Shuai-Shuai; Liu, Wen-Chao; Ma, Yi (Frontiers in Veterinary Science, 2023)
In order to explore the impact of antibiotics (enrofloxacin) on microbial community in aquatic environment, an indoor aquatic ecological model was built, and different concentrations of enrofloxacin (0.05, 0.5, 5, and 50 mg/L) were added in the aquatic ecological model. In addition, the water and sediment samples were collected on the 0, 7, 30, and 60 days, and the changes in microbial community were studied through 16S rDNA high-throughput sequencing. The results showed that when the concentration of enrofloxacin was 50 mg/L, the relative abundance of Actinomycetes was increased. In the water, the bacterial richness and diversity communities first decreased and then gradually recovered with the passage of time; On the 7th day, the diversity and richness index of species in the treatment groups with enrofloxacin at 5 and 50 mg/L decreased to the lowest; On the 30th day, the diversity and richness index of species began to rise; On the 60th day, the diversity index and richness index of water species began to increase, while the diversity index and richness index of sediment species decreased. In conclusion, the addition of enrofloxacin negatively affected the microbial community structure in an indoor aquatic ecological model, 50 mg/L enrofloxacin could increase the relative abundance of Actinomycetes, and decrease the diversity and richness index of water and sediment.